(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the content of theoretical foundations and practical skills of getting rid of excess weight by limiting the calories necessary for the body in the process of fasting through physical exercise, high motor activity. It is intended for those who lose weight by "Starvation", for those who suffer from the disease "obesity" as a result of forming the habit of constantly chewing something in the mouth and eating without stopping.